1999
DOI: 10.1046/j.1365-294x.1999.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation within and between isolated Algerian subpopulations of Barbary macaques (Macaca sylvanus): evidence from microsatellites

Abstract: This study of wild-living Algerian Barbary macaques (Macaca sylvanus) was designed to examine genetic variability in subpopulations isolated in residual forest patches, in an attempt to obtain data on the effects of habitat fragmentation. The wild population of this species (estimated at a maximum of 15,000) is vulnerable and this study therefore has direct relevance for conservation measures. Data from five microsatellite loci were analysed for 159 individuals from nine different groups living in four isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 44 publications
(47 reference statements)
3
22
0
Order By: Relevance
“…Furthermore, the Kherrata population displays the greatest variability despite having the smallest sample size. Similar findings have been reported in a previous study of microsatellites, in which Kherrata was found to have the highest number of private alleles in one social group (32). However, the presence of three markedly divergent mtDNA lineages in Algeria suggests that the observed geographical patterns probably arose through extinction of intermediate populations and physical barriers to dispersal between regions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the Kherrata population displays the greatest variability despite having the smallest sample size. Similar findings have been reported in a previous study of microsatellites, in which Kherrata was found to have the highest number of private alleles in one social group (32). However, the presence of three markedly divergent mtDNA lineages in Algeria suggests that the observed geographical patterns probably arose through extinction of intermediate populations and physical barriers to dispersal between regions.…”
Section: Discussionsupporting
confidence: 89%
“…1). For the Algerian lineages, this finding concords with a previous study based on microsatellites (32). Of particular interest is the initial split occurring at Ϸ1.6 mya, dividing the Moroccan clade and one major Algerian clade from a second major Algerian clade (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It is known that 9 of the latter systems-D1S207, D2S141, D6S311, D7S503, D8S1106, D11S925, D16S420, D17S791, and D18S536-show variation in Barbary macaques (Lathuillière et al, 2001;von Segesser, 1999;von Segesser et al, 1999) and that the 3 remaining systems-D2S305, D3S1279, and D4S243-show polymorphism in other Old World monkeys (Nair et al, 2000;von Segesser, personal communication) and were successfully amplified in M. sylvanus. Most of the microsatellite sequences we examined consisted of CA repeats, but the 3 markers D4S243, D8S1106, and D18S536 contained GATA tetranucleotide repeats.…”
Section: Dna Extraction and Microsatellite Analysismentioning
confidence: 99%
“…Based on fossil and morphological [12], and molecular evidence [13][14][15], Barbary macaques form a separate species group, placed at the base of the clade Macaca, being a sister group to all Asian macaques. Presently, their occurrence is restricted to the mountainous regions of Algeria and Morocco [16,17]. Barbary macaques are largely terrestrial during the day, but climb into trees and sleeping cliffs during the night and also during day-time resting periods [18,19].…”
Section: Introductionmentioning
confidence: 99%